2019
DOI: 10.1088/1755-1315/267/6/062007
|View full text |Cite
|
Sign up to set email alerts
|

Research on the countermeasures of intellectual property protection in the process of resource-based cities’ transformation and upgrading

Abstract: The protection of intellectual property in the process of resource-based cities’ transformation and upgrading is a worldwide problem; China’s large-scale resource-based cities’ transformation process is facing this problem. The research object of this paper is to protect the intellectual property in the process of Daqing City’s transformation and upgrading. This paper inspects the protection of intellectual property in Daqing City in the process of transformation and upgrading and puts forward the specific mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In terms of the IPR, the existing literature investigates the impact of IPR on urban economy, ecological environment, and enterprise competitiveness. He (2019) explore IPR in the process of transformation and upgrading in Daqing city in China. He found that IPR system of Daqing City is not perfect enough, such as lacking IPR professionals, lacking IPR protection awareness, narrow IPR coverage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of the IPR, the existing literature investigates the impact of IPR on urban economy, ecological environment, and enterprise competitiveness. He (2019) explore IPR in the process of transformation and upgrading in Daqing city in China. He found that IPR system of Daqing City is not perfect enough, such as lacking IPR professionals, lacking IPR protection awareness, narrow IPR coverage.…”
Section: Literature Reviewmentioning
confidence: 99%